Kilka uwag o poszerzaniu zakresu merytorycznych kompetencji sądów administracyjnych w świetle art. 184 Konstytucji i konstytucyjnej zasady podziału władz - Kłopocka-Jasińska, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The subject of the article is the issue of possibly broadening the scope of competence of ad-ministrative courts for adjudication on the merits, analysed in the light of constitutional regulations. Against equipping administrative courts with the competence to resolve administrative cases in a wider scope than before, arguments are raised that it is inconsistent with the constitutional notion of „control” contained in Article 184 of the Constitution and the constitutional principle of separation of powers. Analysing the above issues, the author presents a different position indicating that Article 184 of the Constitution cannot be considered in isolation from Article 45 of the Constitution and the guarantees provided therein, which affects the way it is interpreted. In turn, referring to the principle of separation of powers, it is proposed that its aim, which is primarily to protect human rights, should be taken into account and reference should be made to constitutional values such as ensuring the reliability and efficiency of public institutions.
Keywords: administrative judiciary; control of public administration activities; principle of separation of powers; adjudication on the merits by administrative courts; reformatory powers of administrative courts; constitutional right of access to a court